Covalent Adaptable Networks with Tunable Exchange Rates Based on Reversible Thiol–yne Cross‐Linking. (23rd January 2020) - Van Herck, Niels; Maes, Diederick; Unal, Kamil; Guerre, Marc; Winne, Johan M.; Du Prez, Filip E.
Abstract: The design of covalent adaptable networks (CANs) relies on the ability to trigger the rearrangement of bonds within a polymer network. Simple activated alkynes are now used as versatile reversible cross‐linkers for thiols. The click‐like thiol–yne cross‐linking reaction readily enables network synthesis from polythiols through a double Michael addition with a reversible and tunable second addition step. The resulting thioacetal cross‐linking moieties are robust but dynamic linkages. A series of different activated alkynes have been synthesized and systematically probed for their ability to produce dynamic thioacetal linkages, both in kinetic studies of small molecule models, as well as in stress relaxation and creep measurements on thiol–yne‐based CANs. The results are further rationalized by DFT calculations, showing that the bond exchange rates can be significantly influenced by the choice of the activated alkyne cross‐linker. Abstract : Reaktivitätskontrolle : Eine reversible Thiol‐In‐Vernetzung gelingt durch doppelte Michael‐Addition von Thiolen an aktivierte Alkine. Die Geschwindigkeit des dynamischen Thiol‐Austauschs wird durch die Substituenten am aktivierten Alkin moduliert, und die Reaktion bietet eine neue dynamische Plattform für die Entwicklung kovalenter adaptiver Netzwerke.